2015
DOI: 10.1111/febs.13186
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)+ mRNA‐binding protein Tudor‐SN regulates stress granules aggregation dynamics

Abstract: Stress granules (SGs) and processing bodies (PBs) comprise the main types of cytoplasmic RNA foci during stress. Our previous data indicate that knockdown of human Tudor staphylococcal nuclease (Tudor-SN) affects the aggregation of SGs. However, the precise molecular mechanism has not been determined fully. In the present study, we demonstrate that Tudor-SN binds and colocalizes with many core components of SGs, such as poly(A) + mRNA binding protein 1, T-cell internal antigen-1-related protein and poly(A) + m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Some RBPs are essential for SG formation in these species, such as T-cell-restricted intracellular antigen-1 (TIA-1) and TIA-1-related (TIAR) proteins (Gilks et al, 2004), Ras-GTPase-activating protein SH3-domain-binding proteins (G3BPs; Aulas et al, 2015), and Tudor staphylococcal nucleases (TSNs; Gao et al, 2015). Recent studies have revealed the roles of related proteins in plants ( Fig.…”
Section: Mrna Sequestration In Sgs: a Transit Depot Between Translatimentioning
confidence: 99%
“…Some RBPs are essential for SG formation in these species, such as T-cell-restricted intracellular antigen-1 (TIA-1) and TIA-1-related (TIAR) proteins (Gilks et al, 2004), Ras-GTPase-activating protein SH3-domain-binding proteins (G3BPs; Aulas et al, 2015), and Tudor staphylococcal nucleases (TSNs; Gao et al, 2015). Recent studies have revealed the roles of related proteins in plants ( Fig.…”
Section: Mrna Sequestration In Sgs: a Transit Depot Between Translatimentioning
confidence: 99%
“…3 It has also been revealed that TSN is required for the proper aggregation and stabilization of poly(A) + mRNAs, such as those encoding AGTR1 and IGFBP2 (insulin-like growth factor-binding protein 2), in SGs during stress in mammals. 37 In plants, TSN was consistently shown to be required for stabilization of stress-responsive mRNAs under various experimental settings. 36,38,67 These findings demonstrate that TSN-dependent stabilization of specific mRNA molecules is crucial for stress adaptation.…”
Section: Role Of Tsn In Post-transcriptional Regulation Of Gene Exprementioning
confidence: 99%
“…Indeed, both animal and plant TSN proteins interact with several SGassociated proteins 11,12,35,36 and control the fate (stabilization or degradation) of specific mRNAs during stress. 10,[36][37][38] However, lineage-specific intracellular localization of TSN raises doubts about cross-kingdom conservation of all TSN functions. For example, unlike nuclear-cytoplasmic localization of TSN in animal cells, plant TSN is exclusively cytoplasmic, indicating that the probability of its involvement in transcriptional regulation and splicing in plants is low.…”
Section: Structure and Intracellular Localization Of Tsn: Clues To Mumentioning
confidence: 99%
See 2 more Smart Citations